Measurements of Linear and Nonlinear Optical Properties for Iraqi Heavy Crude Oil Samples - Hayder A. Naser; Aseel I. Mahmood; Sawsan K. Fandi (Iraqi Journal of Science, 2021)
In this work, linear and nonlinear optical properties of two types of Iraqi heavy crude oil extracted from fields in southern Iraq were determined. The nonlinear optical properties were measured utilizing Z-scan technology with He-Ne laser at 632.8 nm. It was found that nonlinear refractive index (NLR) values for the Basra and Kut heavy crude oil samples are 6.34381×10-4 and 8.25108×10-4 cm2/mW, respectively, while those for the nonlinear absorption coefficient (NLA) are 2.68942×10-5 and 2.58874×10-5 , respectively. These results showed that the two samples with linear and nonlinear optical properties can be used in optics field applications as optical limiter devices at a wavelength of 632.8 nm.